The Ambit of Terms and Conditions of Employment in Equal Pay Claims Under Section 6(4) of the EEA: Lessons from International Labour Law - Shamier Ebrahim (Potchefstroom Electronic Law Journal)
Section 6(4) of the Employment Equity Act 55 of 1998 (hereafter the EEA) seeks to provide an explicit basis for three types of equal pay claims. It is clear from section 6(4) of the EEA that there are various elements that an equal pay claimant must prove across the three equal pay causes of action. The only element considered in this article is "[a] difference in terms and conditions of employment". No definition is provided in the EEA, the Employment Equity Regulations (GN R595 in GG 37873 of 1 August 2014) or the Code of Good Practice on Equal Pay/Remuneration for Work of Equal Value (GN 448 in GG 38837 of 1 June 2015) as to what would fall within the ambit of "terms and conditions of employment" as referred to in section 6(4) of the EEA. It is important to know what would fall within the ambit of terms and conditions of employment as one of the elements an equal pay claimant must prove is that there is a difference in "terms and conditions of employment". This importance is furthermore evidenced by the fact that an employer can defeat an equal pay claim if it is able to show that the cause of the equal pay complaint does not fall within the ambit of terms and conditions of employment. This article seeks to answer the question as to what falls within the ambit of terms and conditions of employment for the purpose of equal pay claims as contemplated in section 6(4) of the EEA by having reference to domestic and international labour law.